2011
DOI: 10.4314/njbas.v18i2.64334
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fertility Assessment of The Lugu Main Canal Of Wurno Irrigation Project, Sokoto State, Nigeria, Five Years After Rehabilitation.

Abstract: ABSTRACT:A study was conducted during the 2000/2001 irrigation season to assess the soil fertility and the pattern of its variation with depth in the Lugu main canal of Wurno Irrigation Project. Soil samples were collected from four randomly chosen transects across the field at two sampling spots in each transect. The samples were taken at 0 -15, 15 -30 and 30 -45 cm depths from each spot. Soil chemical properties such as pH, total N, available P, CEC and exchangeable bases were determined. The soils had avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The results also showed that soil properties decreased from the surface to the subsurface soil layer (Table 1). This is in line with the findings of Adam et al (2019), Hayatu et al (2019), Popoola and Mgbonu (2018), Yakub andMallo (2018), andDikko et al (2010) who reported that soil pH, cation exchange capacity, organic carbon, organic matter, total nitrogen and available phosphorus decreased with soil depth (from surface to subsurface soil layers). Olubanjo and Inaidoh (2017) also reported that slope position and soil depth significantly influenced soil chemical properties such as pH, N, Ca, Mg, K, H and ECEC.…”
Section: Physico-chemical Properties Pre Biochar Treatment Of Soilsupporting
confidence: 91%
See 2 more Smart Citations
“…The results also showed that soil properties decreased from the surface to the subsurface soil layer (Table 1). This is in line with the findings of Adam et al (2019), Hayatu et al (2019), Popoola and Mgbonu (2018), Yakub andMallo (2018), andDikko et al (2010) who reported that soil pH, cation exchange capacity, organic carbon, organic matter, total nitrogen and available phosphorus decreased with soil depth (from surface to subsurface soil layers). Olubanjo and Inaidoh (2017) also reported that slope position and soil depth significantly influenced soil chemical properties such as pH, N, Ca, Mg, K, H and ECEC.…”
Section: Physico-chemical Properties Pre Biochar Treatment Of Soilsupporting
confidence: 91%
“…The results further showed that the available phosphorus, magnesium, exchangeable acidity and cation exchange capacity increased with soil depth. This however contradicts the findings of Adam et al (2019), Hayatu et al (2019), Popoola and Mgbonu, (2018), Yakub andMallo, (2018), andDikko et al (2010) who reported that soil pH, cation exchange capacity, organic carbon, organic matter, total nitrogen and available phosphorus decreased with soil depth (from surface to subsurface soil layers).…”
Section: Physico-chemical Properties Pre Biochar Treatment Of Soilmentioning
confidence: 65%
See 1 more Smart Citation
“…The methods include Bray1 [1], Mehlich3 [2], acid ammonium oxalate [3], and ammonium acetate. In Nigeria, research on assessment of soil fertility is mainly carried out using Bray1 [4,5,6]. Additionally, the excessive cost of reagents and analytical equipment limits the choice and frequency of collecting soil samples for soil fertility monitoring in Nigerian soils.…”
Section: Introductionmentioning
confidence: 99%
“…The Inductively Coupled Plasma (ICP) technique is generally used to measure the extracted nutrients by the M3 method. For most soil research conducted in Nigeria, however, assessment of soil fertility is done using Bray1 [6,8,10], without consideration to the suitability of the method (soil pH) for accessing the extractable plant nutrients. Also, the researchers generally restrict the application of the method to assessing available P while neglecting other nutrients extracted by the method, thereby leading to wastage of valuable information that would otherwise be available to make scientific soil fertility decisions.…”
Section: Introductionmentioning
confidence: 99%